INTEGRASI AUDIT SEKTOR PUBLIK BERBASIS KINERJA UNTUK MEWUJUDKAN AKUNTABILITAS DAN VALUE FOR MONEY - Anastasya Ayu Swacahayawati; Eskasari Putri (Universitas Prof.Hazairin,SH Bengkulu, 2026)
Accountable public sector management requires audit systems that go beyond compliance and ensure the effective and efficient use of public resources. This study aims to synthesize the role of public sector auditing in enhancing accountability and achieving value for money (VfM). The research employs a Systematic Literature Review (SLR) using the PRISMA protocol, with 14 selected articles forming the basis of analysis. The findings indicate that audit principles, performance auditing, and evidence-based reporting collectively contribute to the achievement of Value for Money by improving economy, efficiency, and effectiveness in public programs. However, challenges remain, including limited auditor independence, the dominance of compliance-based approaches, and low utilization of technology. This study concludes that integrating these audit approaches is essential for strengthening accountability while ensuring the achievement of value for money in public sector governance.